The Role of Growth-Associated Protein-43 (GAP-43) and Superior Cervical Ganglion-10 (SCG-10) mRNA and Protein Levels in Dorsal Root Ganglion Neurons of Lumbar Spinal Cord Segments (L4-L5) Associated with Sciatic Injured Nerve - Ria Margiana (Journal of Global Pharma Technology, 2016)
The analysis focuses on the role of growth-associated protein-43 (GAP-43) and superior cervical ganglion-10 (SCG-10) mRNA and protein levels not only in DRG neurons of lumbar spinal cord segments (L4-L5) associated with sciatic injured nerve. The objective of the research study is to unearth the role of growth-associated protein-43 (GAP-43) and superior cervical ganglion-10 (SCG-10) mRNA and protein level not only in DRG neurons of lumbar spinal cord segments (L4-L5) associated with sciatic injured nerve. The sources were past scientific papers that were published and obtained from google scholar and other sites with open source access. The research review is an original work. The analysis will be centered on a review article that focused on analysis on advantages and disadvantages GAP 43 as neuroregeneration marker examination in rat sciatic nerve injury. The study eligibility criteria was articles that are not older than fifteen years, are written in English and are published. Key words: Sciatic nerve injury, GAP-43, SCG-10 and DRG neurons of L4-L5.